KONSEP DASAR PELAKSANAAN BIMBINGAN KONSELING DI SEKOLAH - Yanti Arsini (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2017)
Counseling guidance is a process of assistance given by BK teachers to students, both individually and in groups to be able to be independent and develop optimally, both in the personal, learning, social and career fields through various types of support services and activities, based on norms which applies to be able to be independent and develop optimally. In the implementation of counseling activities in schools a BK teacher must need to understand correctly and precisely about the basic concept of conducting BK in schools, so that the implementation of BK in schools is in accordance with existing scholarship. Therefore a BK teacher must continue to explore their knowledge about BK itself, so that they become a professional and experienced BK teacher.Keywords: Basic concepts, Implementation, Guidance and Counseling, in Schools